Diphyllobothriasis: the first case report from Malaysia - Mahmud, Rohela; Ibrahim, Jamaiah; Chan, K.W.; Wan Yusoff, W.S. (SEAMEO Regional Tropical Medicine and Public Health Network, 2002)
Diphyllobothriasis is a disease caused by infection with adult tapeworms of the genus Diphyllobothrium. Humans acquire the infection by consuming the raw or inadequately cooked flesh, roe, liver, or other organs of infected fish. Diphyllobothrium latum infection has not been reported in Malaysia; we are reporting the first case. The patient was a 62 year old Chinese male seen at the outpatient clinic with complaints of watery stools and slight abdominal discomfort for four days. Physical examination was normal. He was treated for diarrhea. Two days after treatment, he passed out intact off-white proglottids in his stool. Diphyllobothriasis was confirmed by examination of these gravid proglottids; typical operculated eggs were seen after rupturing the gravid proglottids. The patient had a history of eating sashimi (Japanese raw fish). He was treated with a single dose of praziquantel and had been well since.